Duets encode morphological information from both partners in Rufous Horneros - Pedro Diniz; Paulo S. Amorim (Avian Research, 2025)
Acoustic signals in birds are often influenced by body and beak size (the morphological constraint hypothesis) and may also reflect the sender's condition (the condition dependence hypothesis). However, these ideas have seldom been tested in duetting species, where the acoustics of the combined signal could relate to the morphology of both vocalizing individuals. In this study, we investigated whether specific morphological traits—scaled mass index, wing length, and bill surface area—could predict individual and pair-level characteristics of Rufous Hornero (Furnarius rufus) duets. In this species, partners partially overlap their songs, with males producing faster-paced, lower-pitched songs compared to females. Morphology was most closely associated with the timing of syllables within duets, though different traits were linked to timing in each sex. Females in better condition (indicated by a higher scaled mass index) and with longer wings produced duet phrases with greater variation in syllable duration. In contrast, males with larger bills showed greater variation in both syllable duration and gaps between syllables. The degree of temporal overlap in syllables increased with female condition, but not male condition, suggesting that overlap may signal female quality. Additionally, minimum duet frequency was negatively associated with male condition, indicating that lower-frequency duets may serve as an honest signal of male quality. These findings indicate that the timing of syllables and minimum duet frequency are both condition-dependent and constrained by morphology, allowing receivers to gain multiple insights into the morphology of duetting partners in Rufous Horneros.